Estetisasi Jilbab dalam Ludruk Budhi Wijaya - Maya Rosalinda Krishadianti; Autar Abdillah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The aesthetics of the headscarf on Budhi Wijaya's ludruk aims to show a new form of innovation in the ludruk performance, in which the hijab in the show is used as a support for the characters in the play that is delivered. Ludruk Budhi Wijaya is a millennial ludruk group that accepts all new forms of ludruk performances including the hijab. This study was conducted based on the experience of researchers who were also ludruk players who wore headscarves but were rejected by other ludruk groups because of the limitations of the headscarves worn. descriptive research method using qualitative observer participants as well as participating in the show that was held. The results of the study were then analyzed using the experience theory of Dewiit Hendry Parker, namely subjectivity about the nature of Dewiit Henry Parker's values with four elements that play a role in experience, namely subject, freedom, cause, constant. The results of the research that have been analyzed found that the free and spontaneous response experienced by the subject (artist and audience) related to the hijab in the ludruk performance with the play Faithfulness of a Wife. The existence of a headscarf in the ludruk show also emphasizes the character of the actor in the show